Effective government contracting methods for obtaining advisory services in Iraqi law - Assistant Lecturer Karrar Majeed Hussein Aidan (The college of law and political science journal, 2024)
The need for advisory management and determining effective mechanisms for satisfying it is of importance in light of the continuous technical and scientific development in our contemporary time. Therefore, Iraqi law has dealt with these mechanisms, which begin with a tender and its forms, leading to the method of direct invitation and the method of direct agreement, which the law has written in two forms, the first under the term offer. The only one and the other is represented by the direct contracting method, and finally what is known as procurement committees. Each method has its own terms and conditions of approval that the administration must adhere to in satisfying its consulting needs. The effectiveness of each method varies according to the nature of the required consulting service, its cost, and the circumstances of the need for it. We concluded with this research a number of Effective conclusions and recommendations that specifically address the provisions of the governing law.